2019
DOI: 10.1016/j.jctube.2019.100130
|View full text |Cite
|
Sign up to set email alerts
|

Quality matters: Redefining child TB care with an emphasis on quality

Abstract: Children have been neglected in the fight against tuberculosis (TB) for decades. Despite being the number one infectious disease killer, TB does not feature on the child survival agendas partly due to absent and inaccurate data. Quality is a missing ingredient in TB care in children, yet high rates of unfavorable TB outcomes highlight its importance in this age group. Quality care is particularly important for TB affected children in the absence of a point of care sensitive and specific diagnostic test. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Concerning the quality of care for pediatric TB worldwide, its policies, and academic research, Amanullah et al 41 emphasized the lack of specific approaches for non-adult patients and the shortage of academic interventions for young people aged under 17 years. For the researchers, the low quality of care for young people with TB was evident, and there was no focused and friendly approach to children, adolescents and their families.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the quality of care for pediatric TB worldwide, its policies, and academic research, Amanullah et al 41 emphasized the lack of specific approaches for non-adult patients and the shortage of academic interventions for young people aged under 17 years. For the researchers, the low quality of care for young people with TB was evident, and there was no focused and friendly approach to children, adolescents and their families.…”
Section: Resultsmentioning
confidence: 99%
“…The findings also indicated that a low birth weight, mothers’ education and the child’s age were significant risk factors associated with chronic malnutrition. Despite the high TB-related mortality, childhood TB remains neglected among healthcare workers because of its difficulty to be diagnosed and treated, successfully (Amanullah et al 2019 ). The integrated childhood TB into guidelines for the management of acute malnutrition in high-burden countries further reported that even though the underlying mechanism of the association between malnutrition and TB is unknown, it is reported that about 45% of TB deaths in children are aggravated by malnutrition (Patel & Detjen 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite having policies in practice, childhood TB possibly remains under-identified and underdiagnosed in Bangladesh. It is globally established that diagnosis of childhood TB is a challenge due to the paucibacillary nature of TB, children's incapacity to expectorate sputum and overlapping symptoms with non-TB pneumonia [ 23 , 24 ]. Thus the children initially receive empirical medication [ [25] , [26] , [27] ].…”
Section: Introductionmentioning
confidence: 99%